Bem jurídico penal: proteção e limites à luz da constitucionalização do direito penal - Garmes, Felipe Maiolo (2025)
The present work aims to analyze the concept of criminal legal interest from a constitutional perspective, recognizing the duty of protection attributed to Criminal Law by the Federal Constitution. In this context, the relevance of the principle of prohibiting inefficient protection stands out, which requires the careful identification of legal assets of criminal relevance and the definition of appropriate forms of protection. It is observed that the Brazilian legal system has a hierarchically organized dynamic, which goes from abstraction to the application of individual norms. In this sense, it is essential to analyze the concept of legal good, ensuring that the abstract norm is aligned with constitutional objectives when applied to the specific case, whether in the definition of protection or in the sentence. Furthermore, the study reinforces that Criminal Law must operate as a limit to the State, preventing arbitrariness and ensuring that only truly harmful conduct is criminalized. Thus, the mischaracterization of the Democratic Rule of Law, which is based on the freedom and dignity of the human person, is avoided. The role of criminalization orders, expressed or implicit in the Constitution, is also examined, which impose on the criminal legislator the duty to protect fundamental legal assets, such as life, the environment, and social and diffuse rights. Finally, the Penal State's duty to act and abstain is analyzed, establishing that its actions must be proportional and strictly aligned with constitutional parameters, guaranteeing a balanced and well-founded response